(untitled) (Fiep Bulletin - online, 2013)
It is very fascinating and alluring to our eyes Tuesday as objects of study a phenomenon that has been defined as pleasant, cheerful, fun, free and attractive. Looking then know the games and toys of German culture, which was aimed to understand the way they do for the corporate group. The study then was conducted through a qualitative methodology to provide descriptive and exporatório-based theoretical and methodological principles of ethnographic studies, the analysis of speech and content, with the main objective to verify whether the games and toys identified in the period the school playground still significant traces of German culture playful. Students were involved in the search of initial series of elementary school in the municipal network in the city of Missal / PR, and a couple descended from Germans who were selected because they had the qualities / indicators necessary for the development of research and have full mastery of the language Portuguese, since the subjects older community, for the most part tend to only communicate in their mother tongue which is German. So, to collect the data, using two instruments: interview with no fixed itinerary and a roadmap for comment, also used to the digital camera, recorder, tape and a diary of field. Considering the fact playful with which we encounter and after analysis and interpretations of the findings, we can say that in practice everyday and playful imagination of children Missal there is a significant presence of games and toys what port it is remnants or traces of leisure culture of their ancestors , Pointing to the loss of that cultural trait of the imaginary children of future generations.